2022
DOI: 10.1002/14651858.cd012032.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive surgery for treating pressure ulcers

Abstract: Editorial group: Cochrane Wounds Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 10, 2022.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Meanwhile, the average age of patients with pressure injury has gradually increased, with worse general condition and decreased physical function. For grade III‐IV pressure injury with surgical indications, surgical debridement and surgical reconstruction can greatly help shorten the time of wound healing and hospitalisation 21‐23 . Some elderly patients with pressure injury may not be able to tolerate surgical treatment due to the high risks of surgery and anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the average age of patients with pressure injury has gradually increased, with worse general condition and decreased physical function. For grade III‐IV pressure injury with surgical indications, surgical debridement and surgical reconstruction can greatly help shorten the time of wound healing and hospitalisation 21‐23 . Some elderly patients with pressure injury may not be able to tolerate surgical treatment due to the high risks of surgery and anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The application of physical methods of bedsores therapy is a separate direction of conservative therapy. It is allowed to use one method alone or as a part of complex therapy, the purpose of which is cleaning of tissue debris, pus, and fibrin [17]. Additionally, regenerative processes are stimulated [18].…”
Section: Therapy Methodsmentioning
confidence: 99%
“…39 Several surgical techniques and modifications have been described over the past decades, but limited clinical outcomes data have been published. In a 2022 Cochrane review, 40 only one RCT was identified that investigated the surgical reconstruction of PIs. 41 In this study, Gargano et al 41 enrolled 20 patients randomized to either a conventional flap or a novel cone flap; the novel cone cohort had reduced recurrences compared with the standard flap group.…”
Section: Surgical Intervention For Stage 3 or 4 Pismentioning
confidence: 99%